Chemistry Teachers' TPACK Competence: Teacher Perception and Lesson Plan Analysis - Hayati, Nurlaila; Kadarohman, Asep; Sopandi, Wahyu; Martoprawiro, Muhamad Abdulkadir; Rochintaniawati, Diana (Technium Social Sciences Journal, 2022)
This descriptive study aims to describe chemistry teachers' Technological Pedagogical Content Knowledge (TPACK) competence based on teacher perception and lesson plan analysis. Chemistry teachers' perceptions were obtained through the TPACK questionnaire, which was developed based on components in the TPACK framework. Meanwhile, the lesson plan analysis is carried out through a rubric developed based on the TPACK indicator for the lesson plan. The respondent was 86 chemistry teachers who teach in one Indonesian province. Sampling for the analysis of teacher perceptions was carried out through purposive sampling, and the sample lesson plans were selected from several respondents who filled out the TPACK questionnaire. Both data sets were analyzed descriptively. The results of the TPACK perception analysis of chemistry teachers on the components of TK, PK, and PCK show that they have sufficient ability. These results align with the analysis of the lesson plans they made, which are in the good category. In the CK and TPK components, chemistry teachers' perception shows they have sufficient ability. It is not in line with the results of the analysis of lesson plans which are in the poor category. In TCK component, chemistry teachers' perception shows they have less ability. These results are quite in line with the analysis of lesson plans which are in the very poor category. Finally, the results of the analysis on TPACK component show that chemistry teachers are unsure or doubtful about their abilities, while the results of the analysis of lesson plans are in the very poor category.